Essential basics of dental anatomy and physiology : lab manual ([Cairo] : Cairo University. faculty of oral and dental medicine. oral biology department, 2015)
The discussion sections of the text do an excellent job of deleting extraneous terms and information. It is well written and concise$1! =(Band accomplishes its goal to present essential information. It is fun to read. It is written on a level that I think most college students can easily comprehend.s
Keywords: Teeth; Occlusion (Dentistry).; Tooth -- anatomy & histology; Dental Occlusion; Tooth -- physiology